(untitled) (Educational Perspectives Magazine (REPED), 2023)
The effort made by the Chilean Government through its public policies shows the attempts to inelude all the citizens in the educational system. However, it also shows the actual exclusión since it has taken almost two centuries to be carried out. Chile, today, has 98% of the elementary school population within the educational system (8 years) and nearly 80% of high school population (4 years more of education). There has also been exclusión of the ethnic minorities (Araucanos y Aymaras), which have been taught Spanish and not their vernacular languages. In the last twenty years, a different policy has been implemented in favour of this minority population.